EUROPEAN UNİON’S BEEKEEPING AND HONEY POLICIES (EVALUATION FOR TURKEY IN THE CONTEXT OF SUSTAINABLE COOPERATIVES) (Third Sector Social Economic Review, 2017)
Aim: The aim of this work is, improvement of knowledge level of the EU’s bekeeping and honey policies and helping adoption of the Turkish policies to the EU.Material and Method: In this study, exploration, evaluation methods have been applied. Fort this aim, EU legislation, policies and national programs have been examined and attempted to present an example to our country.Finding: The European Union is the world's second honey producer, and plays an important role in the trade of apiculture products. Beekeeping is practiced in all EU Member States without exception, being characterised by the diversity of production conditions, yields and beekeeping practices. The EU supports this sector through national apiculture programmes in order to improve the production and marketing of honey.Progressing apiculture will contribute to the sustainable growth and development of this sector, bee colonies will continue to act as the providers of important environmental service through pollination, while beekeeping will support the development of rural areas. Beekeeping is a common and important activities in our country, but the share of the economy is not as well as in EU countries and in the United States.Conclusion: EU legislation and 3-year national programs being implemented in the EU Member States examined and have been tried to enlighten to the way of policy makers. If the 3-year program is implemented in Turkey like in the EU, harmonization of the legislation will be realised and  will contribute to the development of our sector via sustainable cooperatives at the same time.
Keywords: EU; Beekeeping; Honey; Policies; Turkey; Cooperation; Sustainability.